PENGARUH LEVERAGE TERHADAP PROFITABILITAS PADA INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Henny Setyo Lestari; Rahmawati Rahmawati (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2009)
This study aims to analyze and determined the relationship of leverage on corporate profitability.The study wanted to analyze the relationship between financial leverage, operating leverage, combined leverage, and debt equity ratio of earning per share. The aim is to explain how the earning capacity gain is influenced by the performance management fixed operating costs and fixed financial costs. In addition this study also explains the relationship between Debt Equity Ratio and Earning Per Share.In this study, selected on food and beverage manufacturing subindustry listed on the Indonesia Stock Exchange during a periode of 11 years from 1999 — 2009. Using Kruskal Wallis testing, spearman correlation analysis and the classical assumption of normality. The result showed that the data DFL, DOL, and DCL didn't differ significantly in manufacturing subindustry. fry the DER and EPS data show that differ significantly in manufacturing subindustry of food and beverages. In addition these studies show that the DFL and DCL have a positive relationship to the EPS, while the DOL and the DER ha.s'a negative relationship to the EPS.Keywords : DCL, DER, DFL, DOL, Earning Per Share, Leverage, and Profitability